ANALISIS KESALAHAN PENGGUNAAN HURUF KAPITAL DAN TANDA BACA PADA KARANGAN NARASI SISWA KELAS V SDN 10 MATARAM TAHUN PELAJARAN 2019/2020 - Hafizah Juzzaini; Ida Ermiana; Syaiful Musaddat (Widya Pustaka : Jurnal Ilmiah Pendidikan, 2020)
This study aims to describe errors in the use of capital letters and punctuation in narrative essays for fifth grade students at SDN 10 Mataram in 2019/2020. The research method used is descriptive qualitative method. The subjects in this study were all the fifth grade students of SDN 10 Mataram as many as 28 students through the narrative essays he made. Data collection techniques in this study are documentation techniques, and tests. The data were analyzed by interactive data analysis. The results of the analysis of errors in the use of capital letters and punctuation in students' narrative essays show that the error rate of students in the capital letter error aspect obtained an average percentage of 79.2% in the high category. Then, in the aspect of punctuation errors, the level of punctuation error aspect obtained an average percentage of 72.2% with a sufficient category, and the types of errors found in students' narrative essays, namely punctuation errors (.), comma punctuation errors. (,), hyphenation errors (-), parentheses punctuation errors ((...)), and quotation marks (“...”).